EFEKTIVITAS MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KETERAMPILAN MENULIS PUISI KELAS IV SD NEGERI 81 PALEMBANG - Wahyu Puspita Dewi; Liza Murniviyanti; Susanti Faipri Selegi (JURNAL HANDAYANI PGSD FIP UNIMED, 2022)
Abstract: This research is motivated by the fact that the poetry writing skills of fourth grade students at SDN 81 Palembang are still low and students are less active in learning activities. The purpose of this study was to determine the effectiveness of the discovery learning model on poetry writing skills in fourth grade students of SDN 81 Palembang. The method used in this research is a pre experimental design with a one group pretest-posttest design. The pretest results obtained an average of 66.5 with the lowest score of 40 and the highest score of 85. The posttest results obtained an average score of 79.3 with the lowest score of 50 and the highest score of 95. The sample used in the study was class IV F with a total of 30 students. . Data collection techniques used in the research are tests and documentation. The data analysis technique used in the study is normality test, homogeneity test and hypothesis testing with a significant level of 5% using Microsoft Excel. Based on the results of the t-test calculation, the thing obtained is 3,947 and the table is 2,001. The criteria for testing the hypothesis are counting labels, then Ho is rejected and Ha is accepted. so it can be concluded that the discovery learning model is effective on the poetry writing skills of fourth grade students of SD Negeri 81 Palembang.Keywords: Discovery Learning, Writing PoetryAbstrak: Penelitian ini dilatarbelakangi fakta bahwa keterampilan menulis puisi pada siswa kelas IV SDN 81 Palembang masih rendah dan siswa kurang aktif dalam kegiatan pembelajaran. Tujuan penelitian ini adalah untuk mengetahui ada tidaknya efektivitas model pembelajaran discovery learning terhadap keterampilan menulis puisi pada siswa kelas IV SDN 81 Palembang. Metode yang digunakan dalam penelitian ini adalah pre experimental design dengan desain one group pretestposttest design. Hasil pretest diperoleh rata-rata 66,5 dengan nilai terendah 40 dan nilai tertinggi 85. Hasil posttest diperoleh rata-rata nilai 79,3 dengan nilai terendah 50 dan nilai tertinggi 95. Sampel yang digunakan dalam penelitian adalah kelas IV F dengan jumlah 30 siswa. Teknik pengumpulan data yang digunakan dalam penelitian yaitu tes dan dokumentasi. Teknik analisis data yang digunakan dalam penelitian yaitu uji normalitas, uji homogenitas dan uji hipotesis dengan taraf signifikan 5% menggunakan microsoft excel. Berdasarkan hasil perhitungan uji-t diperoleh thitung sebesar 3,947 dan ttabel sebesar 2,001. Kriteria uji hipotesis yaitu thitung ≥ ttabel, maka Ho ditolak dan Ha diterima. sehingga disimpulkan bahwa model pembelajaran discovery learning efektif terhadap keterampilan menulis puisi siswa kelas IV SD Negeri 81 Palembang.Kata Kunci: Discovery Learning, Menulis Puisi